Comparison between Process Control Charts and Fuzzy Multinomial Control Charts with Practical Appliance - محمد, زينة معين (Journal of Economics and Administrative Sciences, 2013)
The control charts are one of the scientific technical statistics tools that will be used to control of production and always contained from three lines  central line and upper, lower lines to control quality of production and represents set of numbers so finally the operating productivity under control or nor than depending on the actual observations. Some times to calculating the control charts are not accurate and not confirming, therefore the Fuzzy Control Charts are using instead of Process Control Charts so this method is more sensitive, accurate and economically for assisting decision maker to control the operation system as early time. In this project will be used set data from plant of production of bottles drinking water so designed the fuzzy control charts and also discovering the defectives units as more quickly and accurately. Especially with variable sample size that will product as not constant.